2005
DOI: 10.1017/cbo9780511497582
|View full text |Cite
|
Sign up to set email alerts
|

Changing Conceptions of National Biography

Abstract: The publication of the Oxford Dictionary of National Biography in September 2004 was an event of great literary and scholarly importance. In his Leslie Stephen Lecture, commemorating the founder of the original Dictionary of National Biography, the celebrated historian Keith Thomas surveys the many earlier attempts at collective biography, considers the relationship of the Oxford DNB to them, and offers a preliminary assessment of the Oxford DNB itself. The author, who has been chairman of the Supervisory Com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…For Lee, the Dictionary also served as a record of incremental national progress over time, and especially the century just passed: a charting of 'the multiplication of intellectual callings' by which 'the opportunities of distinction have been of late conspicuously augmented'. 2 Lee's view echoed earlier assessments, including one from Henry Reeve, editor of the Edinburgh Review, for whom the Dictionary's opening volumes offered 'striking proof of the advancement of civilization' that was 'honourably characteristic of the present age'. 3 Ask 'what national biography was for' in 1900 and the answer seems clear: to facilitate national and historical comparisons that revealed the British to be best, and the late Victorian British to be best of all.…”
Section: Philip Cartermentioning
confidence: 85%
See 3 more Smart Citations
“…For Lee, the Dictionary also served as a record of incremental national progress over time, and especially the century just passed: a charting of 'the multiplication of intellectual callings' by which 'the opportunities of distinction have been of late conspicuously augmented'. 2 Lee's view echoed earlier assessments, including one from Henry Reeve, editor of the Edinburgh Review, for whom the Dictionary's opening volumes offered 'striking proof of the advancement of civilization' that was 'honourably characteristic of the present age'. 3 Ask 'what national biography was for' in 1900 and the answer seems clear: to facilitate national and historical comparisons that revealed the British to be best, and the late Victorian British to be best of all.…”
Section: Philip Cartermentioning
confidence: 85%
“…'compare a variety of its modern manifestations', it took place over three days, with the proceedings published as National Biographies and National Identity: A Critical Approach to Theory and Editorial Practice. 2 Musing on the genre in the introduction to the collection, Iain McCalman suggested that the genre of the national biographical dictionary stood 'at the heart of the most ferocious and divisive contemporary debates about the epistemology and hermeneutics of knowledge'. 3 In the late twentiethcentury context of fracturing national identities and the assertion of multiculturalism and multilingualism in Europe and the antipodes, he stated, '[m]akers of national biographies stand in the front line of these identity wars'.…”
Section: Karen Fox March 2019mentioning
confidence: 99%
See 2 more Smart Citations
“…From 1992 onwards, this dictionary became the The Oxford Dictionary of National Biography, and was revised and given a new form. 64 The British model, characterized by its rigorous research and high academic standard, was followed by many later works and is often referenced in thematic dictionaries. It has developed into the Anglophone tradition that today includes the American, Australian, and New Zealand biographical dictionaries.…”
Section: Modal Biographymentioning
confidence: 99%